Highly chemoselective reduction of azides to amines by Fe(0) nanoparticles in water at room temperature. Issue 35 (30th August 2017) - Panja, Subir; kundu, Debasish; Ahammed, Sabir; Ranu, Brindaban C.
Graphical abstract: Highlights: Highly chemoselective reduction of azide to amine at room temperature in water. Use of inexpensive and nontoxic iron nanoparticles. Use of no hydride reducing agent. Tolerance to a wide spectrum of functional groups including S-S linkage. Abstract: A highly chemoselective reduction of aryl, heteroaryl, acyl and sulfonyl azides to the corresponding amines has been achieved by Fe(0) nanoparticles in water at room temperature in the absence of external hydride source. Several readily reducible functionalities including alkene, alkyne, S-S linkage, OTBDMS remain unaffected during reduction.